2024
DOI: 10.1371/journal.pdig.0000341
|View full text |Cite
|
Sign up to set email alerts
|

Large language models approach expert-level clinical knowledge and reasoning in ophthalmology: A head-to-head cross-sectional study

Arun James Thirunavukarasu,
Shathar Mahmood,
Andrew Malem
et al.

Abstract: Large language models (LLMs) underlie remarkable recent advanced in natural language processing, and they are beginning to be applied in clinical contexts. We aimed to evaluate the clinical potential of state-of-the-art LLMs in ophthalmology using a more robust benchmark than raw examination scores. We trialled GPT-3.5 and GPT-4 on 347 ophthalmology questions before GPT-3.5, GPT-4, PaLM 2, LLaMA, expert ophthalmologists, and doctors in training were trialled on a mock examination of 87 questions. Performance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…For instance, a study found GPT-4's diagnostic accuracy comparable to that of board-certified physicians, correctly diagnosing around 98% of cases in a set of 45 clinical vignettes 6 . Similarly, other studies on GPT-4 found that it matched experts in ophthalmology and significantly outperformed non-specialist doctors 7 , it achieved 76.4% in the clinical cases part of the UK Membership of the Royal College of Physicians test 8 , and obtained a perfect score on the National Board of Medical Examiners (NBME) 9 .…”
Section: Discussionmentioning
confidence: 66%
“…For instance, a study found GPT-4's diagnostic accuracy comparable to that of board-certified physicians, correctly diagnosing around 98% of cases in a set of 45 clinical vignettes 6 . Similarly, other studies on GPT-4 found that it matched experts in ophthalmology and significantly outperformed non-specialist doctors 7 , it achieved 76.4% in the clinical cases part of the UK Membership of the Royal College of Physicians test 8 , and obtained a perfect score on the National Board of Medical Examiners (NBME) 9 .…”
Section: Discussionmentioning
confidence: 66%